Hemodynamic Effects of Noninvasive Ventilation in Patients with Venocapillary Pulmonary Hypertension - Bento,André Moreira (2014)
Background: The hemodynamic effects of noninvasive ventilation with positive pressure in patients with pulmonary hypertension without left ventricular dysfunction are not clearly established. Objectives: Analyze the impact of increasing airway pressure with continuous positive airway pressure on hemodynamic parameters and, in particular, on cardiac output in patients with variable degrees of pulmonary hypertension. Methods: The study included 38 patients with pulmonary hypertension caused by mitral stenosis without left ventricular dysfunction or other significant valvulopathy. The hemodynamic state of these patients was analyzed in three conditions: baseline, after continuous positive pressure of 7 cmH2O and, finally, after pressure of 14 cmH2O. Results: The population was composed of predominantly young and female individuals with significant elevation in pulmonary arterial pressure (mean systolic pressure of 57 mmHg). Of all variables analyzed, only the right atrial pressure changed across the analyzed moments (from the baseline condition to the pressure of 14 cmH2O there was a change from 8 ± 4 mmHg to 11 ± 3 mmHg, respectively, p = 0.031). Even though there was no variation in mean cardiac output, increased values in pulmonary artery pressure were associated with increased cardiac output. There was no harmful effect or other clinical instability associated with use application of airway pressure. Conclusion: In patients with venocapillary pulmonary hypertension without left ventricular dysfunction, cardiac output response was directly associated with the degree of pulmonary hypertension. The application of noninvasive ventilation did not cause complications directly related to the ventilation systems.